2015
DOI: 10.1177/0022146515594631
|View full text |Cite|
|
Sign up to set email alerts
|

Marriage, Relationship Quality, and Sleep among U.S. Older Adults

Abstract: Sleep is a restorative behavior essential for health. Poor sleep has been linked to adverse health outcomes among older adults, however, we know little about the social processes that affect sleep. Using innovative actigraphy data from the National Social Life, Health and Aging Project (N=727), we considered the role of marriage, positive marital relationship support, and negative marital relationship strain on older adults’ (aged 62–90) self-reported and actigraph-measured sleep characteristics. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(90 citation statements)
references
References 108 publications
8
77
4
1
Order By: Relevance
“…In addition, we found a correlation between marital status and SD in which married patients are prone to develop insomnia; this is possible considering that a negative marital relationship increased the risk of insomnia symptoms through an increase in mood disorders; these data were confirmed by a previous study (Chen, Waite, & Lauderdale, ).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, we found a correlation between marital status and SD in which married patients are prone to develop insomnia; this is possible considering that a negative marital relationship increased the risk of insomnia symptoms through an increase in mood disorders; these data were confirmed by a previous study (Chen, Waite, & Lauderdale, ).…”
Section: Discussionsupporting
confidence: 88%
“…A study of older adults in China showed an increased risk of short and long sleep duration in unmarried participants . A US study reported better sleep characteristics in older married adults compared with unmarried participants . Conversely, our findings showed participants who were separated/divorced experienced an association with long sleep duration.…”
Section: Discussioncontrasting
confidence: 73%
“…Prior research indicates that married older adults have better actigraph-estimated sleep [47] and married women with metastatic breast cancer have better sleep quality [48]. It may be that HCT recipients who are unmarried are more likely to be sleeping alone; accommodating a caretaker in patients’ homes post-transplant could prove to be disruptive to sleep hygiene.…”
Section: Discussionmentioning
confidence: 99%